2012
DOI: 10.5312/wjo.v3.i12.235
|View full text |Cite
|
Sign up to set email alerts
|

Do osteoporosis-related vertebral fractures precede hip fractures?

Abstract: We recommend that all elderly patients who go to the radiology department for a chest X-ray also have a DEXA scan and a lateral thoracic spine radiograph.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
1
4
0
3
Order By: Relevance
“…[ 6 ] Moreover, the incidence of fragility fractures jumped from 2.9/1000 in 1999 to 6/1000 in 2007 at an annual cost of SR4.27 billion. [ 7 , 8 ] According to El-Desouki, [ 9 ] the prevalence of postmenopausal osteoporosis in the age between 50 and 79 years was 57.5%. Another study by Oommen and AlZahrani [ 10 ] showed that 58% of Saudi women had low bone mineral density (BMD) (18% had osteoporosis and 40% had osteopenia).…”
Section: Introductionmentioning
confidence: 99%
“…[ 6 ] Moreover, the incidence of fragility fractures jumped from 2.9/1000 in 1999 to 6/1000 in 2007 at an annual cost of SR4.27 billion. [ 7 , 8 ] According to El-Desouki, [ 9 ] the prevalence of postmenopausal osteoporosis in the age between 50 and 79 years was 57.5%. Another study by Oommen and AlZahrani [ 10 ] showed that 58% of Saudi women had low bone mineral density (BMD) (18% had osteoporosis and 40% had osteopenia).…”
Section: Introductionmentioning
confidence: 99%
“…Our findings were comparable to that of Sadat-Ali et al who reported a VF in 24.7% of the patients in Saudi Arabia, with more prevalence being in females. 9 As stated by a Norwegian study in 2012, the prevalence of vertebral fractures varies according to age. The study reported the prevalence of VF in women as 3.4% when age <60 years, 11.1% with age 60-69 years and 19.2% with ≥70 years; whereas the prevalence was higher for men; 7.6% with age <60 years, 11.9% with age 60-69 years and 20.3% with ≥70 years.…”
Section: Discussionmentioning
confidence: 96%
“…Так, доведеними факторами ризику переломів ПВСК вважають вік старше від 65 років, належність до жі-ночої статі, попередні переломи в анамнезі, схиль-ність до падінь, сімейний анамнез переломів ПВСК, тривалий прийом глюкокортикоїдів, зловживання алкоголем, дефіцит вітаміну D та наявність деяких соматичних захворювань, зокрема паркінсонізму, цукрового діабету ІІ типу, ревматоїдного артриту та ін. [3,[13][14][15][16][17][18][19][20].…”
Section: âñòóïunclassified
“…Розподіл показника 10-річної ймовірності переломів стегнової кістки в чоловіків та жінок до перелому ПВСК вікових груп більш часто зустрічаються переломи кісток передпліччя, зокрема переломи Колліса, а переломи тіл хребців більш характерні для осіб літного віку. Обидва види переломів у декілька разів збільшують частоту по-вторних переломів, а також інших остеопоротичних пе-реломів [16][17][18][19].…”
Section: îáãîâîðåííÿunclassified
See 1 more Smart Citation